Mining in the international zone and its impact on marine life - Boucetta, Soumeya (Journal of Human Sciences, 2020)
The seabed and oceans outside national jurisdiction are a natural mine for those looking for precious metals. The international seabed authority responsible for regulating mining activities has been granted 29 permits to explore and exploit these minerals. However, mining is a serious threat to marine life in deep plains, hydrothermal vents and cold holes. What is the nature of the effects caused by this phenomenon?This article aims to highlight the most important marine minerals that represent the subject of exploitation by States, as well as the impact of this process on marine life and on the position of the International Seabed Authority.